2001
DOI: 10.1590/s0101-81752001000500006
|View full text |Cite
|
Sign up to set email alerts
|

Fauna parasitária de peixes oriundos de "pesque-pagues" do município de Franca, São Paulo, Brasil. II. Metazoários

Abstract: mesopalamieus that shawed a hi gher susceptibility to Argu/us sp inlestation. lt was not observed significant difference (P > 0.05) in the seasonal variation of L. cyprinacea infection of ali species. L. macrocepho/us, P. mesopolamicus and tambacu showed a great number of P. pi//u/are with no signiticant difference (P > 0.05 ) between them. Manogenean infections were obselved in ali examined spec ies, without significant difference (P > 0.05) in the seasonal variatian. Nevel1he less, occurrence of monagenean w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
3
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 25 publications
4
22
3
8
Order By: Relevance
“…They showed a positive correlation with Kn. This elevated mean intensity was similar to that related in cultured Piaractus mesopotamicus Holmberg, 1884 (Tavares- Dias et al, 2001b) and larger than that related in A. ocellatus in Guandu River, RJ (Azevedo et al, 2007) and ornamental fish from the Negro River, AM (Tavares- Dias et al, 2010). Our results confirm that monogenoideans are among the most common fish parasite that occurs in several environments.…”
Section: Discussionsupporting
confidence: 87%
“…They showed a positive correlation with Kn. This elevated mean intensity was similar to that related in cultured Piaractus mesopotamicus Holmberg, 1884 (Tavares- Dias et al, 2001b) and larger than that related in A. ocellatus in Guandu River, RJ (Azevedo et al, 2007) and ornamental fish from the Negro River, AM (Tavares- Dias et al, 2010). Our results confirm that monogenoideans are among the most common fish parasite that occurs in several environments.…”
Section: Discussionsupporting
confidence: 87%
“…This parasite provokes an excessive production of mucus on the gill filaments, decreasing the respiratory capacity of fish. The prevalence of monogenoideans in the present study was higher than the one found for tambacu cultured in the southeastern region of Brazil (Tavares-Dias et al, 2001b;Martins et al, 2002;Schalch & Moraes, 2005), but the intensity was lower (Tavares-Dias et al, 2001b). Therefore, since these parasites are directly transmitted from fish to fish, the proximity among hosts in ponds might also be important for the successful transmission of this parasite.…”
Section: Resultscontrasting
confidence: 52%
“…The gastrointestinal tract was removed, placed in a Petri dish containing NaCl (0.8%), and examined under a stereomicroscope. The methods used for collection, fixation (Eiras et al, 2006;Thatcher, 2006), and quantification of the parasites (Tavares-Dias et al, 2001a, 2001b were performed according to previous recommendations. The identification of the collected parasites was done according to Díaz-Ungria (1968), Kritsky et al (1979), Thatcher & Paredes (1985), Boeger et al (2002), Belmont-Jégu et al (2004), andThatcher (2006).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations